Microbiological Safety: Evaluation of some Street Vended Ready-to-Eat Fruits Sold in Yenagoa Metropolis, Bayelsa State, Nigeria - Ikpebivie Y. Oku; Ayodele A. Oyedeji; Akuru O. I. (Britain International for Academic Research (BIAR) Publisher, 2020)
Street vended fruits cause food borne illnesses in developing countries. This study was carried out to determine the microbiological safety of some street vended fruits sold in Yenagoa metropolis of Bayelsa State, Nigeria. Freshly cut ready-to-eat vended pawpaw, watermelon and pineapple were analysed for possible contamination with bacteria and fungi using standard microbiological techniques. A total of (17) samples: (5) Pawpaw, (6) Watermelon and (6) Pineapple were obtained from three (3) different local markets in Yenagoa metropolis, namely; Tombia, Opolo and Swali markets. Bacterial count ranged from 1.3x105 to 2.4x106cfu/ml for pineapple; 1.9x105 to 8.1x106cfu/ml for watermelon and 3.7x106 to 7.6x106cfu/ml for pawpaw samples. The highest bacterial count was obtained in watermelon from Opolo market, while the highest fungal count was recorded in pawpaw retailed at Opolo market. Microbial isolates were Bacillus sp, Escherichia coli, Salmonella sp, Staphylococcus sp, Klebsiella spp, Citrobacter spp, Proteus spp, Enterobacter spp, Mucor spp and Saccharomyces cerevisiae. There were 58.8% occurrence of Escherichia coli and Staphylococcus spp and occurred most. Bacillus spp and Klebsiella spp had 47.1% occurrence and closely followed by Staphylococcus aureus 41.2%, while Proteus spp had the least 5.9% occurrence. The result obtained may be responsible for the prevalence of Escherichia coli and Staphylococcus spp in Yenagoa metropolis. The presence of these organisms in these ready-to-eat retailed fruits analysed is a reflection of unwholesomeness and gross contamination of the fruits and therefore make the fruits unsafe for human consumption; hence the need for proper microbiological safety analysis of fruits for human consumption.